2018
DOI: 10.21307/ane-2018-008
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota in neuropsychiatric disorders

Abstract: The purpose of this review is to summarize current knowledge about the gut microbiota in neuropsychiatric disorders. It is estimated that the human gut is colonized by up to 10 18 microorganisms, mostly anaerobic bacteria. The gut microbiome is responsible for multiple functions, e.g. tightness of the intestine barrier, digestion and absorption. The correlation between gut dysbiosis and development of psychiatric, autoimmune and allergic diseases as well as bidirectional communication between brain and gut mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 201 publications
(290 reference statements)
0
42
0
2
Order By: Relevance
“…3 An altered gut microbiome composition not only has been shown linked to the gastrointestinal disorders such as colorectal polyps, 4 colorectal cancer (CRC), 5,6 and celiac disease, 7 but also is associated with non-intestinal disorders such as allergy, 8 asthma, 9,10 obesity, 11,12 non-alcoholic fatty liver, 13 cardiovascular diseases, 13,14 and neuropsychiatric diseases. [15][16][17] These disorders can be attributed to the imbalance of the gut microbiota, which would be referred to as dysbiosis (dysbacteriosis) or dysregulation of gut microbiota. 16…”
Section: Gut Microbiotamentioning
confidence: 99%
“…3 An altered gut microbiome composition not only has been shown linked to the gastrointestinal disorders such as colorectal polyps, 4 colorectal cancer (CRC), 5,6 and celiac disease, 7 but also is associated with non-intestinal disorders such as allergy, 8 asthma, 9,10 obesity, 11,12 non-alcoholic fatty liver, 13 cardiovascular diseases, 13,14 and neuropsychiatric diseases. [15][16][17] These disorders can be attributed to the imbalance of the gut microbiota, which would be referred to as dysbiosis (dysbacteriosis) or dysregulation of gut microbiota. 16…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Indeed, since the concept of bidirectional signalling between the gut and the brain started to evolve, scientists all over the world have made attempts to discover microbial fingerprints in neurology and psychiatry. Emerging research suggested that gut-brain axis dysfunction may be involved in the aetiology of depression and anxiety, schizophrenia, addiction, as well as neurodevelopmental and neurodegenerative diseases and age-related cognitive decline [40][41][42][43][44]. Major microbiota-related alterations in particular neuropsychiatric conditions are summarized in table 1.…”
Section: Microbiota-gut-brain Axis and Susceptibility To Neuropsychiamentioning
confidence: 99%
“…Alterations like dysbiosis generate such weight that have been directly associated with chronic, metabolic, inflammatory non-infectious diseases, and affective disorders of the individual. 1 That is the reason for the current boom in the study of those who help proper maintenance of it, probiotics. The rational use of these, adjunctive tool for various disorders, not only generated an impact according to the nature of its components, but also by environmental changes and due to their antigenic characteristics, signaling for maintenance of the digestive system as the system with better immune performance.…”
Section: Letter To Editormentioning
confidence: 99%